Implementasi Pendekatan Deep Learning Terhadap Pembelajaran Fikih di MTs. Al-Khoirot - Sholihah Sholihah; Khoridatul Bahiyah; Muhammad Zaironi (STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
The deep learning approach, which emphasizes mindful, meaningful, and joyful learning, is considered relevant to addressing the challenges of Fikih instruction that has traditionally focused on rote memorization. However, empirical studies examining the implementation of this approach in Fikih learning at the Madrasah Tsanawiyah level remain limited. This study aims to analyze the implementation of the deep learning approach in Fikih instruction at MTs Al-Khoirot by examining the learning process, supporting and inhibiting factors, and its impact on students’ understanding and religious attitudes. This study employed a qualitative approach with a case study design. Data were collected through classroom observations, interviews with teachers and students, and documentation analysis of instructional materials. Data were analyzed using data reduction, data display, and conclusion drawing, while the trustworthiness of the findings was ensured through source and technique triangulation. The findings reveal that the deep learning approach was implemented through instructional strategies that fostered learning awareness (mindful learning), contextual understanding of Fikih concepts (meaningful learning), and a participatory and enjoyable learning environment (joyful learning). These practices enhanced students’ active engagement, deepened their understanding of Fikih concepts, and strengthened the internalization of religious values reflected in their daily attitudes and behaviors. The study concludes that the deep learning approach has strong potential to improve the quality of Fikih instruction by integrating cognitive, affective, and practical dimensions of learning. The findings contribute to addressing the limited empirical evidence on the implementation of deep learning in Fikih education at the Madrasah Tsanawiyah level and offer an instructional model demonstrating how the integration of mindful, meaningful, and joyful learning can strengthen students’ religious understanding while fostering character development.